The Effectiveness of Mutual Legal Assistance Cooperation at the ASEAN Level as an Effort to Overcome Terrorism Crime: Efektivitas Kerjasama Bantuan Hukum Timbal Balik di Tingkat ASEAN dalam Upaya Penanggulangan Kejahatan Terorisme - Levina Yustitianingtyas; Setyowati, Dewi (Perspektif Hukum, 2025)
Terrorism is included as one of the transnational crimes involving more than one country where there is a legal system and jurisdiction of its implementation, so that cooperation between countries is needed in overcoming this crime. At the ASEAN level, there has been a cooperation agreement, namely the ASEAN Mutual Legal Assistance Treaty. On the other hand, ASEAN member countries have also entered into bilateral agreements in the framework of cooperation in overcoming terrorism crimes.. The research method is normative research with a state approach and a case approach. This legal research aims to examine the extent of the urgency and effectiveness of cooperation in overcoming terrorism crimes at the ASEAN level. The results of this study indicate that although the ASEAN MLA has become an important legal framework in facilitating mutual legal assistance, challenges such as differences in legal systems, levels of trust between countries, and lack of regulatory harmonization are still major obstacles to its effective implementation. Therefore, it is necessary to strengthen the implementation mechanism, increase institutional capacity, and establish a permanent communication forum between law enforcement officers to maximize the role of the MLA in joint efforts to overcome terrorism crimes.